Diversified and Unusual Presentations of Neck Space Infections: Still a Big Concern for Physicians - Laskar, Hanifa A. (J Maxillofac Oral Surg, 2015)
The aim of this clinical study was to find similarities; dissimilarities of neck space infections along with challenges faced by treating physician for their diversified clinical presentations and complications. Patients with neck space infections were compared for the purpose. The classic manifestations of these infections, such as high fever, systemic toxicity, and local signs were not present in all cases leading to dilemma in physician’s decision making. They progress towards fatality very fast. Prompt recognition, diagnosis and management of such cases and complications are of paramount importance to reduce morbidity and mortality. In addition to broad spectrum antibiotic therapy along airway protection, surgical drainage is necessary in nearly all cases. Neck space infections still continue to be a well prevalent health problem in poor socioeconomic group in developing countries having significant morbidity as well as mortality.